MODERN MARKETING AS A TOOL EFFICIENT ACTIVITIES OF THE ENTERPRISE - BONDARENKO, VIKTORIIA; KULAKOVA, SVITLANA; KLYMENKO, KARINA; VERPETA, YAROSLAV (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article presents the substantiation of modern marketing as one of the tools for increasing the effective operation of an enterprise in the new conditions of the economic environment. The authors argue that the use of marketing in the activities of enterprises is the key to the success of business entities, since it allows one to identify and control those factors that determine the conditions for long-term survival and development in the market. Increased competition between business entities in the Ukrainian market has increased the interest of scientists in approaches that ensure the effective functioning of business structures in the new economic environment. Various approaches to the definition of the term "marketing" are considered. The study concluded that the concept of "marketing" is not new in the economic literature of foreign countries. But despite this, there is no specific definition of this concept. In economic culture, this term is interpreted in the form of two basic concepts. Firstly, this is an activity aimed at the development and promotion of products from the very beginning of their production to the final result. Secondly, the concept of "marketing" can be regarded as a complex procedure for the organization and management of an enterprise, aimed at the production of goods and services that are in demand. The content of marketing in the enterprise management system has been investigated. The relationship between marketing and the effective operation of an enterprise has been analyzed. Today, the success of a business is determined by such circumstances as: the futility of covering costs by rising prices presupposes the enterprise's search for ways to reduce its own costs to ensure its compliance with consumer expectations; insufficient fulfillment of the condition of problem-free customer service, who now value the impeccable and immediate satisfaction of their needs; formation of expectations of additional services among clients; the impossibility of achieving success due to limitations in the process of improving the functional characteristics of products. Products and services created with disregard for the individual characteristics of the consumer are now uncompetitive, and the consumers themselves want to participate in creating value. The essence of the marketing concept of enterprise management is investigated and the factors leading to its change, including under the influence of the development of information and Internet technologies, are determined. In particular, attention is focused on the fact that one of the characteristic trends of modern marketing in the XXI century. is the strengthening of the influence of information and Internet technologies on its development. In general, progressive technologization and informatization of economic and everyday life make significant changes in modern marketing, significantly expanding its capabilities, changing the functionality and set of tools necessary to achieve the goals and objectives of companies.
Keywords: marketing; marketing tools; marketing environment; information technology marketing